ACCURACY OF SIZE-SPECIFIC DOSE ESTIMATE CALCULATION FROM CENTER SLICE IN COMPUTED TOMOGRAPHY. Issue 1 (25th May 2017) - Boos, Johannes; Kröpil, Patric; Bethge, Oliver Th; Aissa, Joel; Schleich, Christoph; Sawicki, Lino Morris; Heinzler, Niklas; Antoch, Gerald; Thomas, Christoph
Abstract: To evaluate the accuracy of size-specific dose estimate (SSDE) calculation from center slice with water-equivalent diameter (Dw) and effective diameter (Deff). A total of 1812 CT exams (1583 adult and 229 pediatric) were included in this retrospective study. Dw and Deff were automatically calculated for all slices of each scan. SSDEs were calculated with two methods: (1) from the center slice; and (2) from all slices of the volume, which was regarded as the reference standard. Impact of patient weight, height and body mass index (BMI) on SSDE accuracy was assessed. The mean difference between overall SSDE and the center slice approach ranged from 2.0 ± 1.7% (range: 0–15.5%) for pediatric chest to 5.0 ± 3.2% (0–17.2%) for adult chest CT. Accuracy of the center slice SSDE approach correlated with patient size (BMI: r = 0.15–0.43; weight r = 0.26–0.49) which led to SSDE overestimation in small and underestimation in large patients. SSDE calculation using the center slice leads to an error of 2–5%; however, SSDE is underestimated in large patients and overestimation in small patients.